IMPACT OF DENSITY OF BREEDING ON THE GROWTH AND SOME NUTRACEUTICAL PROPERTIES OF READY-TO-EAT LENTIL (Lens culinaris) SPROUTS - Michał Świeca; Urszula Gawlik-Dziki; Anna Jakubczyk (Acta Scientiarum Polonorum: Hortorum Cultus, 2013)
Nutritional and nutraceutical quality of sprouts is strongly affected by growth conditions. This study focused on determining the influence of breeding density on seedling growth, phenolics content and some antioxidant capacity of ready-to-eat lentil sprouts. Content of condensed tannins (ranging from 1.77 to 3.16 mg g-1 DM) and flavonoids (ranging from 15.13 to 25.08 mg g-1 DM) increased with the increasing density of breeding. The contents of the p-hydroxybenzoic and ferulic acids, and (+) catechin decreased with the increasing density of breeding in 3-days-old seedlings. Additionally, the level of quercetin was elevated at a higher degree in sprouts cultivated at density of 1.22 seeds per cm2 and average 10.42 and 5.91 μg g-1 DM for 3- and 4-days-old sprouts, respectively. Metal chelating ability was the highest for sprouts obtained at the lowest density: 92% and 86% for 3- and 4-days-old sprouts, respectively. Fresh mass yield and lipids preventing abilities were negatively affected by density of breeding. It can be concluded that density of breeding plays an important role in design of chemical composition and bioactivity of lentil sprouts.